Pengaruh Pemberian Pupuk Organik Cair Berbasis Cangkang Telur Ayam dan Pupuk Nitrogen Terhadap Hasil Tanaman Pakcoy (Brassica rapa L subsp. chinensis) Varietas Nauli F1 - Reny Nur Fatimah; Wagiono Wagiono; Darso Sugiono (Jurnal Ilmiah Wahana Pendidikan, 2021)
The pakcoy plant (Brassica rapa L subsp. Chinensi) or also called spoon mustard is a type of leaf vegetable that is classified as mustard. The purpose of this study was to determine the effect of the combination of liquid organic fertilizer from chicken egg shells and nitrogen on the yield of pakcoy (Brassica rapa L subsp. Chinensis) Nauli F1 variety. The experiment was carried out from June to July 2021. The experiment was carried out in the new land of Singaperbangsa Karawang University located in Pasirjengkol Village, Majalaya District, Karawang Regency. The research method used a Randomized Block Design (RAK) consisting of 6 treatments, namely A (Control), B (20% liquid organic fertilizer eggshell + nitrogen), C (40% liquid organic fertilizer chicken eggshell + nitrogen), D ( 60% liquid organic fertilizer chicken egg shell + nitrogen), E (80% liquid organic fertilizer chicken egg shell + nitrogen), and F (POC Nasa). The results of the experiment showed that there was a significantly different effect of giving a combination dose of chicken egg shell liquid organic fertilizer and nitrogen on plant height, number of leaves, leaf area, root length, fresh weight, and dry weight of pakcoy (Brassica rapa L subsp. Chinensis) plants. Nauli F1 variety. Treatment D (60% liquid organic fertilizer chicken eggshell and nitrogen) was able to provide the highest growth and yield of red lettuce on the parameters of plant height, leaf area, fresh weight, and dry weight